Circadian Rhythm of Salivary Cortisol in Obese Adolescents With and Without Apnea: A Pilot Study - Berdina, Olga; Madaeva, Irina; Bolshakova, Svetlana; Sholokhov, Leonid; Rychkova, Liubov (Frontiers in Pediatrics, 2022)
Background and Objective Obstructive sleep apnea (OSA) and obesity are associated with stress system activation involving the hypothalamic-pituitary-adrenal (HPA) axis in adults, but these effects in childhood and adolescence remain unclear. We examined diurnal salivary cortisol as a measurement of the HPA axis function in obese adolescents with and without OSA and the relationships between cortisol levels, body weight, and parameters of polysomnography (PSG). Methods After PSG, saliva samples were collected from obese participants (with and without OSA) and lean participants four times over a 24-h period, namely, at 7:00 h (m-sCort), 13:00 h (a-sCort), 19:00 h (e-sCort), and 23:00 h (n-sCort). An enzyme-linked immunosorbent assay (ELISA) was used to measure salivary cortisol levels. The mean values of cortisol levels and fixed-time point diurnal cortisol slope (DCS) were calculated and compared among the three study groups. Correlations between parameters were analyzed using Spearman's correlation coefficients. Results Obese OSA participants had significantly higher e-sCort and n-sCort levels than both obese non-OSA participants and lean controls. However, m-sCort and a-sCort in these patients had a pronounced upward trend. M-sCort was significantly correlated with both the lowest oxygen saturation (SpO2) and time with SpO2 <90%. Moreover, in the obese OSA group, DCS was significantly flatter than in the other two groups. The a-sCort in obese non-OSA participants was significantly higher than that in the lean control group and, surprisingly, was positively correlated with the apnea/hypopnea index. Additionally, m-sCort was related to body weight. Conclusion This study provided further evidence for alterations in diurnal cortisol production in obese adolescents, which may indicate a chronically stressed HPA axis. However, there were significant differences in salivary cortisol parameters between participants with and without OSA. Furthermore, patients with OSA had more associations between time-point cortisol levels and OSA-related indices. Nonetheless, this research is a pilot study, and further investigations are necessary.